Implications of Down's syndrome on oral health status in patients: A prevalence-based study - Goud, E; Gulati, Saakshi; Agrawal, Akriti; Pani, Pooja; Nishant, K; Pattnaik, Samarjeet; Gupta, Shivam (Journal of family medicine and primary care, 2021)
Background: Down syndrome which is also known as "trisomy 21" is the commonest chromosomal defect that has been associated with intellectual disability or impairment. Clinically, it has been characterized by the generalized presence of hypotonic musculature, variety of neurobiological alterations, numerous respiratory diseases, and significantly higher risk of developing infection along with various dental abnormalities and oro-facial dysmorphological changes. Periodontal diseases are the most prominent oral health issue among individuals diagnosed with Down Syndrome. Aim: The objective of the present prevalence analysis was to study the implications of Down's syndrome on oral health status among patients. Materials and Methods: This was a descriptive and cross-sectional prevalence analysis conducted within a duration of 1 year. A total of 100 children diagnosed with Down syndrome (aged between 5 and 16 years) were selected as the study sample. Inclusion criteria were (a) cytogenetic positive trisomy 21, (b) cooperative behavior, and (c) written informed consent obtained from the legal care-takers. Exclusion criteria were (a) any debilitating form of systemic diseases, (b) any other disability, and (c) extremely uncooperative children. The gingival health status was assessed using gingival index (GI) [Loe and Silness], calculus index (CI) [Ramfjord], and plaque index (PI) [Silness and Loe]. Information involving the practice of oral hygiene maintenance, diet plans, and parental educational status was derived from each parent. Based upon their intelligence quotient (I. Q.) values, the subjects were classified into three groups: a) mild (I. Q. level = 50 to 70), b) moderate (I. Q. level = 35 to 50), and c) severe (I. Q. level ≤35). Statistical analysis was performed using the statistical software tool Statistical Package for Social Sciences (SPSS) version 20.0. Qualitative data were recorded as frequencies, and percentages and quantitative data were recorded as mean and standard deviation values. All categorical outcomes were analyzed by means of the Chi-square test. The quantitative outcomes of Calculus Index, Gingival Index, and Plaque Index were analyzed by either student's t-test or one-way analysis of variance (ANOVA). Significance was set at a cut-off value of P < 0.05. Results: Down syndromic children between 12 and 16 years were reported to have statistically significant higher Calculus Index, Gingival Index, and Plaque Index values in comparison with younger age syndromic children (P < 0.01). Those with severe mental retardation had significantly higher Plaque Index (P < 0.001) and Gingival Index (P < 0.04) values when compared with those with mild and moderate mental retardation. No significant difference in comparing Calculus Index was noted. Conclusion: Higher age group children with Down syndrome require close monitoring by parents for assisting in maintaining oral hygiene practices just as in younger age group children.